Theoretical prediction of mass transfer coefficients in both gas–liquid and slurry bubble columns. (10th January 2017) - Nedeltchev, Stoyan
Abstract: The gas–liquid contact time has been defined in a new way (bubble surface-to-rate of surface formation) and the range of applicability of the penetration theory in both gas–liquid and slurry bubble columns has been examined. In both reactors, the mass transfer coefficients were predicted successfully not only in the homogeneous regime but also in the heterogeneous regime (superficial gas velocities up to 0.08 ms −1 ). The results in the article demonstrate the importance of the geometrical characteristics (length and height) of the oblate ellipsoidal bubbles for the accurate calculation of the contact time and thus the volumetric liquid-phase mass transfer coefficient k L a . The gas–liquid interfacial area has been calculated in both reactors in the classical way, i.e. as a function of the gas holdup and inversely proportional to the Sauter-mean bubble diameter. It was found that in the gas–liquid bubble column (0.095 m in ID) the modified penetration theory was applicable to tap water, 9 organic liquids (decalin, nitrobenzene, 2-propanol, 1, 4-dioxane, ethanol (99%), tetralin, xylene, 1, 2-dichloroethane, ethylene glycol) and two liquid mixtures (water-glycol and tetralin-ethanol). Tetralin was aerated with both nitrogen and helium, whereas xylene was aerated with hydrogen and helium. The correction factor introduced by Calderbank (1967) was found useful for improving the k L a predictions in 1, 2-dichloroethane, ethanol (99%), xylene(-hydrogen) and toluene–ethanol 97.2%. In the case of a slurry bubble column, the new approach was found applicable (at low solids concentrations) to four different gas–liquid–solid systems: air–tetralin–Al2 O3, air–water–Al2 O3, air–water-activated carbon and air–Na2 SO4 –kieselguhr. It is noteworthy that in some cases (air–water-Al2 O3 ) the new definition of the contact time was found applicable up to solids concentrations of 6.29%. In the case of a slurry bubble column, it was found that when the theoretical k L a value is multiplied by the inverse value of the correction factor the predictions improve with about 5%. Finally, in the slurry bubble column the contact time was defined on the basis of the length of the micro-eddies and the k L a values in both air–water-alumina and air–water-activated carbon systems were successfully predicted. This is also a potentially good approach. Highlights: New definition of gas–liquid contact time. Applicability range of the modified penetration theory. Role of the correction factor. Operation of a gas–liquid bubble column with organic liquids. Operation of a slurry bubble column with four different systems.